10 - Ethnicisation du domaine public et construction de l’État : pistes pour transcender une antinomie - Yenshu Vubo, Emmanuel (Africa Development, 2021)
The problem of relations between the ethnic fact and the phenomenon of ethnicity on the one hand, and the state on the other hand, is posed here in terms of the particularism/universalism dilemma in modern politics, in which the construction of the public sphere is central. By reviewing the different theories on ethnicity and examining the political construction of ethnicity in the dynamics of the construction of African states, I seek to lay down some foundations for transcending the apparent conflict between the particularisms born of ethnic diversity and the universalist process of construction of the state. Other than the political ethics of recognizing multiculturalism, I also propose the management of diversity based on another vision of ethnicity that advocates a depoliticization of ethnicity and a reform of the state.